Biofunctool® Approach Assessing Soil Quality under Conservation Agriculture and Conventional Tillage for Rain- fed Lowland Rice Systems in Cambodia - TIVET, FLORENT; THOUMAZEAU, ALEXIS; SAR, VENG; RATTANAPICHAI, WUTTHIDA; SAJJAPHAN, KANNIKA; SENG, VANG (International Journal of Environmental and Rural Development, 2022)
Rice productivity is often limited by soil fertility depletion, water availability and access. Conservation Agriculture (CA) cropping systems have been designed and tested with the main objectives of restoring soil fertility, increasing productivity and profitability. This study assessed changes in soil health under rain-fed lowland rice under (i) conventional tillage (CT), (ii) CA (CA7: 7 years under CA) and (iii) green manure management for one year (CGM1) and for two years CGM2). Biofunctool®, a multi-functional soil assessment approach based on a set of seven soil indicators, was used to evaluate changes in three main soil functions (C transformation, nutrient cycling, and soil structure). In addition, soil chemical analyses were conducted in the 0-5, 5-10, 10-20 and 20-40 cm soil layers to assess changes in nutrient contents. Our results emphasized positive impacts of CA on C transformation, soil structure and nutrient contents. Soil organic carbon and total N were significantly higher (p < 0.05) under CA7 in the 0-5 cm layer with up to +7.5 g C kg-1 and +0.74 g N kg-1, respectively. Higher values of labile C and soil respiration (p < 0.05) were observed under CA in the 0-5 and 5-10 cm layers. More stable soil aggregates and improved VESS values (p < 0.05) were also observed under CA. CA and CGM had 2 to 3 times more available phosphorus than CT in the 0-5 cm layer, and higher values were observed under CA from a depth of 0-20 cm. Higher Ca, Mg and K contents were recorded under CA and CGM in the 0 to 40-cm soil layer. A SOC stabilization trend was observed in soils under CA (0-5 and 5-10 cm layers) while a SOC mineralization trend was observed under CT and CGM. These results emphasize the positive impacts of CA on maintaining and/or enhancing soil health and in contributing to SOC accumulation. A diachronic analysis is now needed to assess the long-term on-farm impacts of CA on soil health and crop performances.